2017
DOI: 10.18844/prosoc.v4i2.2753
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative variables associated with extubation time in patients undergoing open heart surgery

Abstract: Decreasing mechanical ventilation and early extubation in patients has many clinical benefits. Hence, an awareness of some variables, associated with extubation time can help nurses to plan convenient care aimed at making a safe and early extubation. The purpose of this study was to investigate whether any intraoperative variables had a significant effect on extubation time following open heart surgery. The research was conducted on 60 open heart surgery patients who met inclusion criteria between April 2014 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Postoperative intubation time of patients may be affected by some individual and disease characteristics. In the literature, it has been reported that age, total perfusion time, aortic cross-clamping time, total operation time, minimum body temperature, use of inotropic agents, use of intraaortic balloon pump, amount of drainage, and blood transfusion are among the factors prolonging the postoperative extubation time [9,26]. Delayed extubation may cause delayed mobilization and prolong the LOS in the ICU and hospital [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative intubation time of patients may be affected by some individual and disease characteristics. In the literature, it has been reported that age, total perfusion time, aortic cross-clamping time, total operation time, minimum body temperature, use of inotropic agents, use of intraaortic balloon pump, amount of drainage, and blood transfusion are among the factors prolonging the postoperative extubation time [9,26]. Delayed extubation may cause delayed mobilization and prolong the LOS in the ICU and hospital [1].…”
Section: Discussionmentioning
confidence: 99%
“…This form consists of some questions created by the researchers, including some demographic characteristics such as age, gender, and working time of the nurses. FORM 2: Patient Observation Form This form consists of 25 questions created by the researchers, including some demographic (13 questions) and surgical (12 questions) characteristics of patients admitted to the CVS-ICU after cardiac surgery, and IMS [9].…”
Section: Data Collection Tools Form 1: Nurse Data Formmentioning
confidence: 99%